Pengetahuan Kesehatan Reproduksi Remaja Dalam Mencegah Perilaku Seksual Beresiko - Rizawati (Jurnal Amanah Kesehatan, 2023)
Adolescence is a stage of growth after puberty to adulthood, and also a transitional period from childhood to adulthood. The city of Padang ranks third with the most teenagers having risky sexual behavior after Payakumbuh and Bukittinggi, and the Civil Service Police Unit (Satpol PP) of the City of Padang arrested 12 pairs of teenagers who were not husband and wife at several jasmine inns in the city of Padang. The purpose of this study was to see how the level of knowledge of SMA Pertiwi students regarding sexual risk behavior is described. This type of research is descriptive which was carried out at Pertiwi Padang High School in January-July 2022. The population of all Class VIII students is 101 people. The sampling technique is proportional random sampling with a total sample of 50 people. Data collection using a questionnaire. Then the data were analyzed univariately. The results showed that 20% of students had a low level of knowledge about the meaning of sexual risk behavior. As much as 30% of students have a low level of knowledge about sources of information on sexual risk behavior. 32% of students have a low level of knowledge about the causes of sexual risk behavior. 34% of students have a low level of knowledge about types of sexual risk behavior and 6% of students have a low level of knowledge about the impact of sexual risk behavior. It is hoped that the school will activate PIK R to help students get reproductive health information